Turkish External Orientation and Political Culture - Yiallourides, Christodoulos K.; Langides, Afendoulis T. (Études helléniques / Hellenic Studies, 2012)
Tis article focuses on the challenges the Turkish Republic is facing, the most severe to its post-Ottoman existence. In terms of political culture Turkey appears to be dithering between the West and Asia, between a secular state and Islam. Te political system is showing signs of vacillating between Islam and Europe, raising doubts about the main strategic directions established by Mustafa Kemal and his successors.In terms of foreign policy a “Neo-Ottoman” foreign policy could not possibly be separated from the strong inﬂuence of Islam internally. A “zero problem” policy towards it’s immediate environment, which means de-emphasizing problems with surrounding countries, such as Syria, Iran, and Greece, inspired by Ahmet Davutoğlu, a former academic and the present foreign minister of the Turkish republic, initially seemed promising and bearing fruits. Tis is not any more the case and Turkey has to defend itself against the claims that in it’s essence, it’s a Neo-Ottoman policy of regional domination.